Late Holocene stratigraphic evolution and sedimentary facies of an active to abandoned tide‐dominated distributary channel and its mouth bar. Issue 3 (29th September 2021) - Gugliotta, Marcello; Saito, Yoshiki; Ta, Thi Kim Oanh; Nguyen, Van Lap; La Croix, Andrew D.; Wang, Zhanghua; Tamura, Toru; Nakashima, Rei; Lieu, Kim Phuong
Abstract: To better understand the sedimentary facies of tide‐dominated deltas, a core dataset from the Ba Lai palaeochannel in the Mekong River Delta was obtained and studied. Nine sedimentary facies were identified and interpreted as representing the Late Holocene evolution of the Ba Lai palaeochannel, including its pre‐abandonment and post‐abandonment phases, as well as pre‐channel phases. The channel formed at 2.6 ka as a distributary channel connected to the deltaic network and was abruptly abandoned and rapidly infilled with sediment at 0.7 ka. The channel deposits are up to ca 11 m thick and overlie shelfal shell layers, which, in turn, overlie Mid‐Holocene and Pleistocene deposits. The active‐channel fill and mouth‐bar deposits consist of sand and mud with cyclical patterns, bidirectional lenses and abundant mud layers, suggesting deposition mainly driven by river and tidal processes. The abandoned‐channel fill consists entirely of organic‐rich mud, suggesting a predominance of tidal processes. Other sedimentary facies include tidal‐flat and marsh deposits; they mostly consist of mud and formed in shallow to subaerial areas near the channel margins or on barforms. Depending on the exact location of the core in this depositional setting, three possible stratigraphic successions and facies models are presented herein. Near channel margins, the deposits show an upward gradual change from heterolithic to mud with a well‐developed fining‐upward trend. Away from the channel margins, the deposits show an upward sharp change from heterolithic to mud due to the channel abandonment. The mouth‐bar‐area facies model shows an upward gradual change from heterolithic to heterolithic/sand to mud deposits with a coarsening‐upward to fining‐upward trend. Although differences among systems likely exist, the authors suggest that the sedimentary facies described in this study and the resulting facies models should be used to better understand tide‐dominated deltaic systems and to improve their interpretation in the geological record.